3(y-1)=1

Simple and best practice solution for 3(y-1)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-1)=1 equation:


Simplifying
3(y + -1) = 1

Reorder the terms:
3(-1 + y) = 1
(-1 * 3 + y * 3) = 1
(-3 + 3y) = 1

Solving
-3 + 3y = 1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3y = 1 + 3

Combine like terms: -3 + 3 = 0
0 + 3y = 1 + 3
3y = 1 + 3

Combine like terms: 1 + 3 = 4
3y = 4

Divide each side by '3'.
y = 1.333333333

Simplifying
y = 1.333333333

See similar equations:

| 14+3(r)=2 | | 94=4pir^2 | | 10x-83=-8x+97 | | 4r+1= | | 10x-83l=-8x+97 | | 5(2r)=7 | | 1-3x+4x=4 | | 1=-2x+x-8 | | 3x^2+6x-20=0 | | 2+ln(x+3)=4 | | 3*cos(2*x-1)=0 | | 2x+2(x-4)=28 | | 8+5+r=3 | | 2+ln(x+3)=2 | | 4y-15=29 | | x-3/2+1=x | | (6*r)-9=12 | | 2+on(x+3)=2 | | 550=(.3t^2)+11.5t | | 2ln(3x)=20 | | cos^2x+5cos(x)=1 | | 4-(x-8)=3x+2(x-1) | | 2+6x+3x=65 | | r+2+9=12 | | 9y+7=88 | | -x+2x+7x=74 | | -47=5x+2x+2 | | 5(z-1)(-z-4)=0 | | 6d+5=4d+9 | | 5(v-4)-5=-2(-4v+5)-9v | | 2(x+3)=x+3 | | 2w+3w-324=0 |

Equations solver categories